The Peruvian criminal procedural model - Ventocilla Ricaldi, Edwin Francisco (2020)
The Code of Criminal Procedure has adopted its own criminal procedural model, mixed, in that it exceptionally granted the judge powers and functions of the parties to the proceedings; where the JIP Judge without being the director of the investigation may order the completion of a supplementary investigation indicating the period and the procedures that the prosecutor must perform; also the Judge of Judgment and sentence without being the holder of the burden of proof may order the realization of an inspection or reconstruction and order the performance of new evidence.